VD_FINDINFO HC / 2024 / 793 vom 9. Dezember 2024 - VD Tribunal cantonal (2024)
COURTAGE, CONSTATATION DES FAITS, PARTAGESENS GÉNÉRAL, VENTE, LIEN DE CAUSALITÉ | 412 al. 1 CO, 413 al. 1 CO, 106 al. 2 CPC (CH)